Good manufacturing practices of minimally processed vegetables reduce contamination with pathogenic microorganisms - Iriani Rodrigues Maldonade; Verônica Cortez Ginani; Roberta Figueiredo Resende Riquette; Rodrigo Gurgel-Gonçalves; Vinícios Silveira Mendes; Eleuza Rodrigues Machado (Revista do Instituto de Medicina Tropical de São Paulo, 2019)
ABSTRACT Consumption of ready-to-eat (RTE) vegetables is quick, easy and healthy, especially when eaten without cooking. However, they might be a source of foodborne pathogenic microorganisms. The objective of this study was to evaluate the microbiological and parasitological contamination of fresh RTE vegetables produced in agroindustries in the Federal District of Brazil (FD), and to correlate contamination with good manufacturing practices (GMP). One hundred and three samples of RTE vegetables were collected from six agroindustries for microbiology and parasitology analyses and correlate with GMP; 54 samples were collected from three hypermarkets for parasitological evaluation. None of the samples analyzed were positive for Salmonella sp. and for thermotolerant coliforms, but they were contaminated with total coliforms. All analyzed samples were contaminated with at least one species of enteroparasistes or commensals, which were identified as Ascaris sp., Balantidium coli, Entamoeba histolytica/dispar, Hookworm, Strongyloides sp., Trichuris sp., Entamoeba sp., eggs and larvae of Nematoda, insects and fungi. Agroindustries that adopted GMP showed less contamination with helminths. RTE vegetables sold in hypermarkets of the FD are unfit for human consumption. It is important to guide farmers in the FD on the need to adopt good practices in the production and processing of vegetables to reduce the microbial contamination.